2020
DOI: 10.7554/elife.59465
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell atlas of the mouse and human prostate reveals heterogeneity and conservation of epithelial progenitors

Abstract: Understanding the cellular constituents of the prostate is essential for identifying the cell of origin for prostate adenocarcinoma. Here we describe a comprehensive single-cell atlas of the adult mouse prostate epithelium, which displays extensive heterogeneity. We observe distal lobe-specific luminal epithelial populations (LumA, LumD, LumL, and LumV), a proximally-enriched luminal population (LumP) that is not lobe-specific, and a periurethral population (PrU) that shares both basal and luminal features. Fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
160
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(187 citation statements)
references
References 61 publications
(126 reference statements)
15
160
2
4
Order By: Relevance
“…We demonstrate that these RUNX1 + PLCs exhibit a greater organoid forming potential compared to the remaining luminal fraction, consistent with previous reports isolating similar proximal populations using different markers such as SCA-1, TROP2 or CD26 (Crowley et al, 2020;Goldstein et al, 2008;Guo et al, 2020;Karthaus et al, 2020;Kwon et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We demonstrate that these RUNX1 + PLCs exhibit a greater organoid forming potential compared to the remaining luminal fraction, consistent with previous reports isolating similar proximal populations using different markers such as SCA-1, TROP2 or CD26 (Crowley et al, 2020;Goldstein et al, 2008;Guo et al, 2020;Karthaus et al, 2020;Kwon et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Here, we identified a subset of RUNX1 + luminal cells located in the proximal region of the developing and adult prostate, referred to as RUNX1 + PLCs, and corresponding to the Lum-D cluster identified in our adult scRNA-seq dataset. Of note, this subset appears to be the equivalent of the 'L2' (Karthaus et al, 2020) or 'LumP' (Crowley et al, 2020), or 'Lum-C' (Guo et al, 2020) clusters identified in recent studies. In light of the extensive contribution of RUNX transcription factors to developmental processes (Mevel et al, 2019), our study suggests that Runx1, but also Runx2, may be involved in the development and maintenance of specific subpopulations of the prostate epithelium.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Simultaneously, others performed singlecell transcriptomics analyses on mouse prostate tissues, and some also validated their findings in benign human prostate tissues that were obtained from adult men (Crowley et al 2020, Guo et al 2020, Karthaus et al 2020. Collectively, these efforts have confirmed the presence of previously unrecognized and functionally diverse prostate epithelial cell populations, which an initial comparative analysis of the transcriptome data sets from these distinct studies has started to reconcile (Crowley et al 2020). The incorporation of mouse models verified the AR-dependence and the regenerative potential of these cell populations in organoid, tissue recombination and in vivo studies (Crowley et al 2020, Karthaus et al 2020, which uncovered that prostate regeneration can be driven by nearly all luminal cells that persist in the prostate after castration, not just rare stem cell populations.…”
Section: Proliferative Potential Of Prostate (Cancer) Cellsmentioning
confidence: 84%
“…A pioneering study performed single-cell RNA-seq analyses on benign prostate tissues of healthy young men and uncovered five epithelial cell types, which includedin addition to basal, luminal and NE cell types -also two novel epithelial cell types that are enriched in the prostate urethra and proximal prostatic ducts (Henry et al 2018). Simultaneously, others performed singlecell transcriptomics analyses on mouse prostate tissues, and some also validated their findings in benign human prostate tissues that were obtained from adult men (Crowley et al 2020, Guo et al 2020, Karthaus et al 2020. Collectively, these efforts have confirmed the presence of previously unrecognized and functionally diverse prostate epithelial cell populations, which an initial comparative analysis of the transcriptome data sets from these distinct studies has started to reconcile (Crowley et al 2020).…”
Section: Proliferative Potential Of Prostate (Cancer) Cellsmentioning
confidence: 97%